Incorporation of Controlled Islanding Scenarios and Complex Substations in Optimal WAMS Design - Ghamsari-Yazdel, Mohammad; Esmaili, Masoud; Aminifar, Farrokh; Gupta, P.; Pal, Anamitra; Shayanfar, Heidarli (IEEE transactions on power systems, 2019)
An efficient wide-area measurement system (WAMS) should be able to preserve system observability in foreseen abnormal situations, such as intentional controlled islanding (ICI). In this paper, an optimal WAMS design model is proposed while ensuring power system observability in the base case and all plausible scenarios of ICI. Thus, quasi-observable states that are undesirable in state estimation are avoided. The model minimizes the cost of substation disruptions imposed by PMU installation and the cost of WAMS components subject to diverse economic and technical constraints. In order to optimally retain system observability in different operational configurations of substations, complex buses of switchgears with bus sectionalizers and couplers are modeled. Also, the indeterminacy of transformer tap ratios is considered to have realistic solutions. The proposed method is examined on IEEE standard test systems as well as Polish 2383-bus and 2746-bus large-scale systems to demonstrate its applicability to real systems.